Perancangan UI/UX Aplikasi Mobile Sangkara Menggunakan Metode Lean UX - Putra, I Gede Aldi Kusuma; Paramitha, A A Istri Ita; Purnama, I Nyoman (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Startups are companies that have not been running for a long time, and some of these companies or startups have just been established and are in the phase of developing and exploring the market. The development of startups in the world started from around the '90s to the 2000s. Sangkara is a startup operating in the environmental sector. Sangkara was formed on December 29. Sangkara currently has an official website, but Sangkara plans to develop its technology by creating a mobile application. Mobile applications usually have an attractive and simple user interface so they can provide fast and easy service. Before developing a mobile application, designing the user interface and user experience needs to go through the prototyping stage. To support the creation of the Sangkara mobile application prototype, the Lean UX method was used which contains 4 stages, namely declare assumption, Create an MVP, Run an Experiment and feedback and Research. This method was chosen because it focuses on user satisfaction with the prototype design of the mobile application that will be designed. After going through each stage of Lean UX and testing using the usability scale (SUS) system, the UI/UX design of the Sangkara mobile application has been accepted by users, potential users and Sangkara staff with avegare SUS score is 89.